1.1: Invited Paper: TFT Backplane for Display. (28th November 2018) - Shieh, Han-Ping D.
Abstract : Thin Film Transistors (TFT) are being widely used as backplane to drive display components, such as LCD, OLED, and even u‐LCD. A‐Si, poly Si, oxide, and organic are common materials for TFT. Mobility, scale‐up and long term stability are among the key concern for TFT. Vertical channel thin film transistors (VTFTs) are proposed as an effective approach to reduce driving voltage and power consumption for achieving high speed and high resolution displays. Considering that oxide semiconductors have large‐area compatible processes, it will be better to find a method for achieving low driving voltages with conventional optical lithography machines used for large area display panels. In this talk, we will review the state of art of the vertical TFTs and explore the major fabrication issues. In addition, we will examine amorphous indium gallium zinc oxide (a‐IGZO) vertical channel TFT fabricated at low temperature to evaluate the impact of gate dielectric on electric characteristics of the vertical vis‐à‐vis planar TFTs. VTFTs employing vertical amorphous a‐IGZO channel of 500 nm have been fabricated without additional photolithography process. The various issues related to the improved device performance will be addressed. Solution based organic TFT will also be examined to explore its feasibility for backplane to drive display and other components.